EVALUASI KETERBUKAAN INFORMASI PUBLIK PADA ERA DIGITAL MENURUT UNDANG-UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK (STUDI PADA BADAN PUSAT STATISTIK KABUPATEN PANDEGLANG) - Muchsinin Muchsinin (LPPM Universitas Djuanda Bogor, 2022)
The Central Statistics Agency (BPS) of Pandeglang Regency as a Public Agency, one of which plays a role in providing information as a form of fulfilling the rights of citizens. One form of public service, BPS Pandeglang Regency provides facilities through a website to make it easier for the public to access the data and information needed, without having to come directly to BPS Pandeglang Regency. The purpose of the study was to evaluate the disclosure of information on public services BPS Pandeglang Regency. The research method used is through interview techniques and literature study. The results of the study indicate that the disclosure of information through the website has not been implemented optimally, which can be seen from the data and information presented is not always updated due to limited human resources and the availability of secondary data that depends on other public agencies. The conclusion is that the disclosure of public information through the website at the BPS Pandeglang Regency has not been implemented optimally, so that the rights of citizens to obtain up-to-date information on the demands of the digital era have not been fulfilled.